2021
DOI: 10.5614/itbj.ict.res.appl.2021.15.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Cell Selection Mechanism Based on Q-learning Environment in Femtocell LTE-A Networks

Abstract: Universal mobile networks require enhanced capability and appropriate quality of service (QoS) and experience (QoE). To achieve this, Long Term Evolution (LTE) system operators have intensively deployed femtocells (HeNBs) along with macrocells (eNBs) to offer user equipment (UE) with optimal capacity coverage and best quality of service. To achieve the requirement of QoS in the handover stage among macrocells and femtocells we need a seamless cell selection mechanism. Cell selection requirements are considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Bathich, A. A. and others found that after the 1970s, with the deepening of people's understanding of the importance of natural environment and ecosystem, nature reserves, as a specific area divided for the protection of natural resources and ecological environment, have gradually attracted the attention of the international community [ 5 ]. Liu, X. and others found that China established the first nature reserve in 1956.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bathich, A. A. and others found that after the 1970s, with the deepening of people's understanding of the importance of natural environment and ecosystem, nature reserves, as a specific area divided for the protection of natural resources and ecological environment, have gradually attracted the attention of the international community [ 5 ]. Liu, X. and others found that China established the first nature reserve in 1956.…”
Section: Literature Reviewmentioning
confidence: 99%